Practices and Attitudes That Enhance Music Engagement of Adult Cochlear Implant Users - Gfeller, Kate; Mallalieu, Ruth MacMullen; Mansouri, Aleksander; McCormick, Gaelen; O’Connell, Renee Blue; Spinowitz, Jake; Gellinek Turner, Bettina (Frontiers in Neuroscience, 2019)
Background Cochlear implants (CIs) are auditory prostheses designed to support spoken communication in persons with severe to profound hearing loss. Many post-lingually deaf adult CI users achieve good speech recognition in quiet; unfortunately, CI technology conveys a degraded representation of pitch and timbre, essential components of music. Not surprisingly, most CI users achieve significantly poorer perception and enjoyment of music compared with normal hearing listeners. Anecdotal evidence indicates that this impacts music engagement, particularly singing and playing instruments requiring ongoing tuning to external pitches or producing intervallic ratios. Interestingly, a small cohort of adult CI users has shown remarkable success in recovering or developing musical skills, but their success is poorly understood. Greater understanding of their efforts and attitudes may suggest potential rehabilitative approaches for other CI users. Purpose This article documented personal characteristics and experiences perceived to contribute to high level musicianship. Research questions included: (1) What forms of practice/experience have most contributed to (re)establishing satisfying music making? (2) What situations or musical tasks are most frustrating or challenging? (3) What attitudes, motivational factors, or forms of support help CI users persist in working toward improved music engagement? Methods Qualitative and patient–engaged research methodologies were used. Our study involved a unique collaboration of six CI users engaged in high levels of musicianship and a researcher whose scholarship focuses on music and CIs. The CI recipients conveyed their experiences and attitudes regarding music and CIs through open-ended narratives. These narratives were analyzed using an integrative approach of inductive and deductive coding methods. The codes and themes that emerged through inductive methods were then organized within the Dynamic Problem Solving Model for Management of Music Listening Environments (Gfeller et al., 2019a). Outcomes: This paper provides reflections of six CI users who successfully engage in active music making, including on-going tuning to external pitches and ensemble participation. Their perspectives emphasize the importance of pre-CI music instruction, extensive practice and immersion in music listening and playing, persistence and self-efficacy, and problem solving skills that optimize music engagement, and suggest possible strategies useful to other CI users interested in improving music experiences.